Use of metal organic framework material as 1,3-butadiene adsorbent and method for adsorptive separation of carbon four hydrocarbon mixture
Patent Information
- Application Number
- CN202410334412.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-03-21
AI Technical Summary
可见,开发兼顾高容量、高选择性,且具有优秀稳定性的高效丁二烯吸附剂仍具有很大挑战性
[0038]本发明提供了一种采用金属有机框架材料吸附分离碳四烃混合物的新方法,可基于碳四烃分子的三维尺寸差异和表面静电势差异实现分子辨识分离,在该类材料中,丁二烯的扩散速率明显高于其他碳四烃组分,能够实现碳四烃混合物中1,3-丁二烯的高效脱除,并且可以实现痕量1,3-丁二烯的捕获,分离后流出的碳四物料中丁二烯含量极低。
Smart Images

Figure CN118059541B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of adsorption separation technology, and more particularly to the application of metal-organic framework materials as 1,3-butadiene adsorbents and a method for adsorbing and separating mixtures of C4 hydrocarbons. Background Technology
[0002] The C4 fraction mainly contains the following components: n-butane (n-C4H) 10 ), isobutane (iso-C4H) 10 The distillates include 1,3-butadiene (C4H6), 1-butene (or n-butene, n-C4H8), cis-2-butene (cis-2-C4H8), trans-2-butene (trans-2-C4H8), and isobutene (iso-C4H8), which are mainly derived from byproducts of ethylene production via hydrocarbon steam cracking and catalytic cracking in oil refineries, with smaller amounts derived from natural gas and oilfield recoveries. Among these, 1,3-butadiene, isobutene, and 1-butene, used as intermediates for product purity standardization, have a significantly higher industrial value than other fractions, especially when their polymer-grade purity reaches 99.5% or higher. 1,3-Butadiene (abbreviated as butadiene) is primarily used in the production of synthetic rubbers such as chloroprene rubber, cis-butadiene rubber, styrene-butadiene rubber, and nitrile rubber. It is also used in the synthesis of ABS resin, SBS resin, BS resin, MBS resin, and other organic chemical products. It has wide applications in the production of fine chemicals and is an important basic chemical raw material. The level of butadiene processing and utilization is also an important indicator of the development level of the petrochemical industry. n-Butene can be used to synthesize resin plastics such as polyethylene and poly-1-butene; it can also be used to produce fine chemical products such as plasticizers, surfactants, and pesticides; high-concentration n-butene can also be used as an anesthetic. Isobutylene is an important raw material for fine chemicals. High-purity (>99%) isobutylene is widely used as a monomer or intermediate in the production of methacrylonitrile, butyl rubber, and polyisobutylene, while 90% purity isobutylene can be used to produce methacrylic acid, isoprene, etc. Therefore, the efficient separation of C4 hydrocarbon mixtures to obtain individual high-purity C4 olefin products has significant industrial value. Furthermore, the C4 hydrocarbon mixtures produced by catalytic cracking processes contain low concentrations of 1,3-butadiene (0–0.5% by mass), which easily leads to equipment coking and blockage. Selectively capturing low concentrations of 1,3-butadiene is also of great importance.
[0003] Currently, industrial methods for separating C4 hydrocarbon mixtures mainly include cryogenic distillation, extractive distillation, solvent absorption, and molecular sieve adsorption. 1,3-Butadiene is typically separated using extractive distillation or solvent absorption, such as using acetonitrile, dimethylformamide, or methylpyrrolidone solvents for absorption or extractive distillation to produce high-purity 1,3-butadiene. However, these methods suffer from drawbacks such as significant organic solvent loss, environmental unfriendliness, and high energy consumption. Furthermore, 1,3-butadiene is prone to polymerization at high temperatures, potentially leading to serious safety issues such as explosions. Therefore, a new and ideal alternative separation method is needed, and adsorption separation technology based on highly efficient adsorbents, as an energy-saving and environmentally friendly separation technology, holds promise for achieving this goal.
[0004] In recent years, Chinese patent CN102329180A has disclosed a method for preparing isobutylene using adsorption separation. This method uses calcium-modified 5A molecular sieves as the adsorbent, employs a multi-stage bed adsorption method, and uses n-hexane and heptane as desorbents to separate isobutylene from C4 materials. Chinese patent CN104030874A has disclosed a process for separating n- and isobutylene based on carbon molecular sieve adsorption. This process uses three-tower or multi-tower pressure swing adsorption with a pore-adjustable carbon molecular sieve as the adsorbent to achieve high-purity separation of n- and isobutylene. Chinese patent CN102351630A uses barium or potassium-modified X or Y-type zeolite molecular sieves to selectively adsorb 1-butene from liquid-phase C4 materials. In summary, while traditional adsorbents such as molecular sieves can achieve partial separation of C4 components, it is difficult to obtain high-purity butadiene products, and there is also the problem of balancing adsorption capacity and separation selectivity.
[0005] Metal-organic frameworks (MOFs), as an emerging class of adsorbent materials, have attracted widespread attention in the field of adsorption and separation due to their advantages such as high porosity, easily tunable pore structures, and readily functionalizable surfaces. To date, various MOFs have been reported for the separation of C4 mixtures. However, for the separation of C4 olefin mixtures, the reported MOFs generally suffer from difficulties in simultaneously achieving high capacity, selectivity, and stability. Regarding the challenge of efficiently and specifically capturing butadiene under low concentration conditions, existing material solutions are particularly scarce, with few reports of materials that can meet this requirement. Therefore, developing highly efficient butadiene adsorbents that balance high capacity, high selectivity, and excellent stability remains a significant challenge. Summary of the Invention
[0006] In view of this, the present invention provides the application of metal-organic framework materials as 1,3-butadiene adsorbents and a method for adsorbing and separating mixtures of C4 hydrocarbons. The present invention uses a metal-organic framework material with the structure shown in Formula I as a 1,3-butadiene adsorbent, which has high adsorption capacity, high selectivity, and excellent stability, enabling efficient separation of 1,3-butadiene from C4 hydrocarbon mixtures.
[0007] To achieve the above-mentioned objectives, the present invention provides the following technical solution:
[0008] The application of metal-organic framework materials as 1,3-butadiene adsorbents, wherein the general structural formula of the metal-organic framework material is shown in Formula I:
[0009] ML2(A) Formula I;
[0010] In Formula I: A represents anion, including SiF6 2- TiF6 2- GeF6 2- ZrF6 2- SnF6 2- ,NbOF5 2- MDS 2- EDS 2- PDS 2- and BDS 2- At least one of the following; M is a metal ion, including Cu 2+ Fe 2+ Co 2+ Ni 2+ and Zn 2+ At least one of them;
[0011] L is an organic ligand, with the structural formula shown in Formula II:
[0012]
[0013] In Formula II: R1 to R8 are independently selected from H, F, Cl, Br, I, CH3, NH2, -OH or -COOH.
[0014] The present invention also provides a method for adsorbing and separating a mixture of C4 hydrocarbons, comprising the following steps: using a metal-organic framework material as an adsorbent to adsorb and separate 1,3-butadiene from the C4 hydrocarbon mixture; wherein the C4 hydrocarbon mixture includes 1,3-butadiene, and further includes at least one of n-butene, isobutene, n-butane, isobutane, cis-2-butene, and trans-2-butene;
[0015] The general structural formula of the metal-organic framework material is shown in Formula I:
[0016] ML2(A) Formula I;
[0017] In Formula I: A anion, including SiF6 2- TiF6 2- GeF6 2- ZrF6 2- SnF6 2- ,NbOF5 2- MDS 2- EDS 2- PDS 2- and BDS 2- At least one of the following; M metal ions, including Cu 2+ Fe 2+ Co 2+ Ni 2+ and Zn 2+ At least one of them;
[0018] L is an organic ligand, with the structural formula shown in Formula II:
[0019]
[0020] In Formula II: R1 to R8 are independently selected from H, F, Cl, Br, I, CH3, NH2, -OH or -COOH.
[0021] Preferably, the adsorption separation temperature is -20 to 100°C and the pressure is 0 to 1000 kPa.
[0022] Preferably, the metal-organic framework material is an amorphous particle, spherical particle, columnar particle, or membrane.
[0023] Preferably, the adsorption separation method is one or more of fixed bed adsorption, fluidized bed adsorption, moving bed adsorption, simulated moving bed adsorption, and membrane separation.
[0024] Preferably, the synthesis method of the metal-organic framework material includes solid-state grinding, interfacial slow diffusion, solvothermal method, room temperature coprecipitation method, or microwave synthesis method.
[0025] Preferably, the solvothermal method includes: reacting organic ligand L, anion A, and metal ion M in a liquid reaction system to obtain the metal-organic framework material; the metal ion M is added in the form of a soluble salt containing metal ion M; and the anion A is added in the form of a soluble salt or acid containing anion A.
[0026] Preferably, the reaction temperature is -20 to 100°C, and the time is 0 to 48 hours, and not 0.
[0027] Preferably, after the adsorption separation, the adsorbent is further desorbed to obtain butadiene-rich product; the desorption method includes desorption under reduced pressure, desorption under elevated temperature or gas purging.
[0028] The present invention also provides a metal-organic framework material, the general structural formula of which is shown in Formula I:
[0029] ML2(A) Formula I;
[0030] In Formula I: A anion, including SiF6 2- TiF6 2- GeF6 2- ZrF6 2- SnF6 2- ,NbOF5 2- MDS 2- EDS 2- PDS 2- and BDS 2- At least one of the following; M metal ions, including Cu 2+ Fe 2+ Co 2+ Ni 2+ and Zn 2+ At least one of them;
[0031] L is an organic ligand, with the structural formula shown in Formula II:
[0032]
[0033] In Formula II: R1 to R8 are independently selected from H, F, Cl, Br, I, CH3, NH2, -OH or -COOH;
[0034] Where M, L, and A are not all Cu 2+ SiF6 2- and 4,4'-methylene bipyridine, and not simultaneously Cu 2+ GeF6 2- And 4,4'-methylene bipyridine.
[0035] This invention provides the application of metal-organic framework materials as 1,3-butadiene adsorbents, the general structural formula of which is shown in Formula I. The metal-organic framework material used in this invention has a layered structure, prepared from metal ions, inorganic / organic anions, and organic ligands, and possesses a dual-channel structure both intralayer and interlayer. Its intralayer conformation, interlayer stacking mode, and spatial geometric distribution of anions can be precisely controlled by changing the types of anions and cations. It can achieve molecular recognition and separation based on the three-dimensional size differences and surface electrostatic potential differences of C4 hydrocarbon molecules, specifically capturing 1,3-butadiene, and exhibits high adsorption capacity, high selectivity, and excellent stability.
[0036] The present invention also provides a method for adsorbing and separating a mixture of C4 hydrocarbons, using a metal-organic framework material as an adsorbent to adsorb and separate 1,3-butadiene from the C4 hydrocarbon mixture; the C4 hydrocarbon mixture includes 1,3-butadiene, and also includes at least one of n-butene, isobutene, n-butane, isobutane, cis-2-butene, and trans-2-butene; the general structural formula of the metal-organic framework material is shown in Formula I.
[0037] The main advantages of this invention compared to existing technologies include:
[0038] This invention provides a novel method for adsorbing and separating C4 hydrocarbon mixtures using metal-organic framework materials. This method can achieve molecular recognition and separation based on the differences in the three-dimensional size and surface electrostatic potential of C4 hydrocarbon molecules. In this type of material, the diffusion rate of butadiene is significantly higher than that of other C4 hydrocarbon components, which can achieve efficient removal of 1,3-butadiene from the C4 hydrocarbon mixture and capture trace amounts of 1,3-butadiene. The butadiene content in the C4 material after separation is extremely low.
[0039] Compared with conventional adsorbents, the metal-organic framework material used in this invention can achieve dynamic exclusion of n-butene, isobutene, n-butane, isobutane, cis-2-butene and trans-2-butene, and has a high capacity for butadiene adsorption in the low-pressure region.
[0040] The metal-organic framework material used in this invention has good air, water, and thermal stability, can be recycled, and has potential for industrial applications. Furthermore, this type of metal-organic framework material has advantages such as simple synthesis method, mild synthesis conditions, easy batch preparation, and easy molding.
[0041] Compared with traditional solvent absorption, extractive distillation and cryogenic distillation technologies, the separation method provided by this invention has the advantages of low energy consumption, small equipment investment and environmental friendliness.
[0042] Furthermore, the present invention can obtain high-purity 1,3-butadiene products according to industrial needs. After desorption, 1,3-butadiene products with a purity greater than 99.5% can be obtained, with the highest purity greater than 99.99%. Attached Figure Description
[0043] Figure 1 Thermogravimetric curves of the SiFSIX-dpm-Cu layered MOF material obtained in Example 1 are shown.
[0044] Figure 2 The powder X-ray diffraction pattern of the SiFSIX-dpm-Cu layered MOF material obtained in Example 1 after being placed in water / air for one week;
[0045] Figure 3The kinetic curves of the SiFSIX-dpm-Cu layered MOF material obtained in Example 1 for C4 hydrocarbons at 298 K and 1 bar are shown.
[0046] Figure 4 Thermogravimetric curve of the EDS-dpm-Cu layered MOF material obtained in Example 2;
[0047] Figure 5 The powder X-ray diffraction pattern of the EDS-dpm-Cu layered MOF material obtained in Example 2 after being placed in water / air for one week;
[0048] Figure 6 The kinetic curves of the EDS-dpm-Cu layered MOF material obtained in Example 2 for C4 hydrocarbons at 298 K and 1 bar are shown.
[0049] Figure 7 Thermogravimetric curve of the MDS-dpm-Cu layered MOF material obtained in Example 3;
[0050] Figure 8 The powder X-ray diffraction pattern of the MDS-dpm-Cu layered MOF material obtained in Example 3 after being placed in water / air for one week;
[0051] Figure 9 The kinetic curves of the MDS-dpm-Cu layered MOF material obtained in Example 3 for C4 hydrocarbons at 298 K and 1 bar are shown.
[0052] Figure 10 The penetration curve is shown in Example 4.
[0053] Figure 11 The penetration curve is shown in Example 5.
[0054] Figure 12 The penetration curve is shown in Example 6.
[0055] Figure 13 This is the penetration curve for Example 7. Detailed Implementation
[0056] This invention provides an application of a metal-organic framework material as a 1,3-butadiene adsorbent, wherein the general structural formula of the metal-organic framework material is shown in Formula I:
[0057] ML2(A) Formula I;
[0058] In Formula I: A is an anion, including SiF6 2- TiF6 2- GeF6 2- ZrF6 2- SnF6 2- ,NbOF52- MDS 2- (methanedisulfonate), EDS 2- (1,2-Ethylene disulfonate), PDS 2- (1,3-propanedisulfonate) and BDS 2- At least one of (1,4-butanedisulfonic acid); M is a metal ion, including Cu. 2+ Fe 2+ Co 2+ Ni 2+ and Zn 2+ At least one of them;
[0059] L is an organic ligand, with the structural formula shown in Formula II:
[0060]
[0061] In Formula II: R1 to R8 are independently selected from H, F, Cl, Br, I, CH3, NH2, -OH or -COOH.
[0062] In this invention, the metal ion M is simultaneously bridged with the organic ligand L and the anion A through coordination bonds to form a single-layer network structure, and adjacent layers are stacked through supramolecular interactions to form a layered two-dimensional metal-organic framework structure.
[0063] In this invention, the metal ion M is preferably Cu. 2+ The anion A is preferably SiF6. 2- MDS 2- and EDS 2- At least one of the following; in the organic ligand L, R1, R2, R3, R4, R5, R6, R7, and R8 are independently selected from any one of H, F, Cl, Br, I, CH3, NH2, OH, or COOH. Further, the organic ligand L is preferably 4,4'-dipyridylmethane (CAS No.: 60776-05-8, hereinafter referred to as dpm). With the above combination of metal ion M, anion A, and organic ligand L, the resulting material can better achieve efficient capture of 1,3-butadiene, while simultaneously achieving dynamic exclusion of n-butene and isobutene.
[0064] In a specific embodiment of the present invention, the metal-organic framework material in which the metal ion M is Cu 2+ Anion A is SiF6 2-The organic ligand L is 4,4'-methylene bipyridine (dpm), denoted as SiFSIX-dpm-Cu. The saturated adsorption capacities of this material for 1,3-butadiene, n-butene, and isobutene at 1 bar and 298 K are 2.00 mmol·g⁻¹, respectively. -1 1.80 mmol·g -1 2.00 mmol·g -1 The equilibrium times to reach saturation adsorption were 10 min, 300 min, and 600 min, respectively.
[0065] As a specific embodiment of the present invention, in the metal-organic framework material, the metal ion M is Cu. 2+ Anion A is MDS 2- The organic ligand L is 4,4'-methylene bipyridine (dpm), denoted as MDS-dpm-Cu. The saturated adsorption capacities of this material for 1,3-butadiene, n-butene, and isobutene at 1 bar and 298 K are 1.80 mmol·g⁻¹, respectively. -1 1.73 mmol·g -1 2.00 mmol·g -1 The equilibrium times to reach saturation adsorption were 5 min, 20 min, and 200 min, respectively.
[0066] As a specific embodiment of the present invention, in the metal-organic framework material, the metal ion M is Cu. 2+ Anion A is EDS 2- The organic ligand L is 4,4'-methylene bipyridine (dpm), denoted as EDS-dpm-Cu. The saturated adsorption capacities of this material for 1,3-butadiene and n-butene at 1 bar and 298 K are 1.86 mmol·g⁻¹, respectively. -1 and 1.92 mmol·g -1 The equilibrium times to reach saturation adsorption were 100 min and 1000 min, respectively. For isobutylene, adsorption equilibrium was not reached even after 5000 min, at which point the adsorption capacity was 1.52 mmol / g.
[0067] In this invention, the synthesis method of the metal-organic framework material preferably includes solid-state grinding, interfacial slow diffusion, solvothermal method, room temperature coprecipitation method or microwave synthesis method, with solvothermal method being preferred.
[0068] In this invention, the solvothermal method preferably includes: reacting organic ligand L, anion A, and metal ion M in a liquid reaction system to obtain the metal-organic framework material; the metal ion M is added in the form of a soluble salt containing metal ion M; this invention does not have special requirements on the type of soluble salt of metal ion M, and any salt well known to those skilled in the art can be used. In a specific embodiment of this invention, when metal ion M is Cu... 2+ When using copper tetrafluoroborate as the soluble salt, the preferred soluble salt is added in the form of a soluble salt or acid containing anion A. This invention does not have specific requirements regarding the specific type of the soluble salt or acid containing anion A; any salt or acid well-known to those skilled in the art can be used. In a specific embodiment of this invention, when anion A is SiF6... 2- When using ammonium hexafluorosilicate as the preferred soluble salt, and when the anion A is MDS 2- When using this method, the preferred soluble salt is disodium methanedisulfonate, and when anion A is EDS. 2- The preferred soluble salt used is disodium 1,2-ethanedisulfonate; the molar ratio of the organic ligand L, anion A, and metal ion M is preferably 2:1:1; the solvent used in the liquid reaction system is preferably water and / or an organic solvent, the organic solvent being preferably an alcohol solvent, more preferably methanol; in a specific embodiment of the present invention, the liquid reaction system is preferably provided by a water-methanol mixed solvent, the volume ratio of water to methanol in the water-methanol mixed solvent is preferably 1:1; the reaction temperature is preferably -20 to 100°C, more preferably 0 to 50°C, further preferably room temperature, and the reaction time is preferably 0 to 48 h, and not 0, more preferably 24 h.
[0069] In a specific embodiment of the present invention, it is preferable to first dissolve the soluble salt or acid of anion A and the soluble salt of metal ion M in water to obtain an aqueous solution, dissolve ligand L in methanol to obtain a methanol solution of ligand L, and then add the methanol solution of ligand L dropwise to the aqueous solution, and carry out a stirring reaction at the above temperature.
[0070] After the reaction is completed, the present invention preferably filters the obtained product liquid, soaks the obtained solid product in anhydrous methanol and then dries and degasses it to obtain the metal-organic framework material; the soaking time is preferably 3 days, and the anhydrous methanol is preferably replaced once a day during the soaking process; the drying and degassing is preferably carried out under vacuum conditions, the drying and degassing temperature is preferably 373K, the vacuum degree is preferably <1Pa, and the time is preferably 24h.
[0071] In this invention, when the metal-organic framework material is used as a 1,3-butadiene adsorbent, it specifically adsorbs and separates 1,3-butadiene from a mixture of C4 hydrocarbons.
[0072] This invention also provides a method for adsorbing and separating a mixture of C4 hydrocarbons, comprising the following steps: using a metal-organic framework material as an adsorbent to adsorb and separate 1,3-butadiene from the C4 hydrocarbon mixture; the C4 hydrocarbon mixture includes 1,3-butadiene, and further includes at least one of n-butene, isobutene, n-butane, isobutane, cis-2-butene, and trans-2-butene; the general structural formula of the metal-organic framework material is shown in Formula I (see above); the structure and preparation method of the metal-organic framework material shown in Formula I are consistent with the above scheme, and will not be repeated here.
[0073] In this invention, the metal-organic framework material is an amorphous particle, spherical particle, columnar particle, or membrane; this invention does not have special requirements for the preparation method of metal-organic framework materials of different morphologies, and methods well known to those skilled in the art can be used.
[0074] In this invention, the volume ratio of 1,3-butadiene, n-butene, isobutene, n-butane, isobutane, cis-2-butene, and trans-2-butene in the C4 hydrocarbon mixture is arbitrary. The C4 hydrocarbon mixture may also contain impurities such as hydrogen, nitrogen, oxygen, carbon oxides (e.g., carbon monoxide, carbon dioxide), water, and other low-carbon hydrocarbons (e.g., methane, butane). These impurities do not affect the adsorption and separation performance of the layered metal-organic framework material for the C4 hydrocarbon components.
[0075] In a specific embodiment of the present invention, the content of 1,3-butadiene in the C4 hydrocarbon mixture is preferably 0-60%, and not 0; the C4 hydrocarbon mixture is preferably a mixture of 1,3-butadiene, n-butene, and isobutene; when the C4 hydrocarbon mixture comes into contact with the metal-organic framework material of the present invention, due to the difference in molecular size and surface electrostatic potential, the adsorbent selectively adsorbs 1,3-butadiene molecules and excludes other C4 molecules, thereby achieving efficient separation of 1,3-butadiene, and the purity of the separated butadiene product can reach up to 99.99%.
[0076] In this invention, the adsorption separation temperature is preferably -20 to 100°C, more preferably 15 to 60°C, and even more preferably room temperature; the pressure is preferably 0 to 1000 kPa, more preferably 0 to 500 kPa, and even more preferably 0 to 200 kPa.
[0077] In this invention, the adsorption separation method is preferably one or more of fixed bed adsorption, fluidized bed adsorption, moving bed adsorption, simulated moving bed adsorption, and membrane separation, and more preferably fixed bed adsorption; the adsorption separation can be carried out by temperature swing adsorption or pressure swing adsorption, and this invention does not make specific limitations.
[0078] In this invention, when a fixed-bed adsorption separation is performed, the following steps are preferably included:
[0079] The metal-organic framework material is packed into a fixed-bed adsorption column, and a mixture of C4 hydrocarbons is passed into the fixed-bed adsorption column. The fast-diffusing 1,3-butadiene component is adsorbed in the pores of the metal-organic framework material, while the slow-diffusing C4 component penetrates the adsorption column first. After the 1,3-butadiene penetrates the adsorption column, the adsorption separation ends.
[0080] In this invention, when a fixed bed method is used for adsorption separation, the metal-organic framework material is preferably amorphous particles or shaped spherical particles.
[0081] After adsorption and separation, the present invention preferably further includes desorption of the adsorbent to obtain butadiene-rich product; the desorption method includes desorption under reduced pressure, desorption under elevated temperature, or gas purging; the pressure of desorption under reduced pressure is preferably 0-1 bar, more preferably 0-0.1 bar, and the temperature of desorption under elevated temperature is preferably 10-200°C, more preferably 25-120°C, more preferably 50-120°C; the gas used for gas purging is preferably nitrogen, inert gas, pure butadiene gas, or the gas of the separated product; the inert gas is preferably He or Ar; the gas purging temperature is preferably 20-100°C, more preferably 60-100°C; the performance of the adsorbent remains unchanged after desorption and it can be recycled; the purity of the butadiene-rich product obtained after desorption reaches the polymerization grade purity; the polymerization grade purity refers to a purity greater than 99.5%, and the highest purity is greater than 99.99%.
[0082] The present invention also provides a metal-organic framework material, the general structural formula of which is shown in Formula I:
[0083] ML2(A) Formula I;
[0084] In formula I: A is SiF6 2- TiF6 2- GeF6 2- ZrF6 2- SnF6 2- ,NbOF5 2- MDS 2- EDS 2- PDS 2- and BDS 2- At least one of them; M is Cu 2+ Fe 2+ Co 2+ Ni 2+ and Zn 2+ At least one of them;
[0085] L is an organic ligand, with the structural formula shown in Formula II:
[0086]
[0087] In Formula II: R1 to R8 are independently selected from H, F, Cl, Br, I, CH3, NH2, -OH or -COOH;
[0088] Where M, L, and A are not all Cu 2+ SiF6 2- and 4,4'-methylene bipyridine, and not simultaneously Cu 2+ GeF6 2- And 4,4'-methylene bipyridine.
[0089] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0090] Example 1
[0091] Using a room-temperature stirring method, 1.0 mmol of 4,4'-methylene bipyridine (170 mg) was dissolved in 10 mL of anhydrous methanol, and 0.50 mmol of copper tetrafluoroborate hydrate (118.5 mg) and 0.50 mmol of ammonium hexafluorosilicate (89 mg) were dissolved in 10 mL of water. The ligand methanol solution was added dropwise to the aqueous solutions of the metal salt and anionic salt, and the reaction was stirred at room temperature for 24 h to obtain a mixed solution of blue-violet solid products. The liquid was then filtered, and the solid product was soaked in anhydrous methanol for three days, with the methanol solution being replaced once a day during this period. After drying and degassing under vacuum (<1 Pa) at 373 K for 24 h, the SiFSIX-dpm-Cu layered MOF material was obtained.
[0092] The thermogravimetric curve of the SiFSIX-dpm-Cu layered MOF material obtained in this embodiment is as follows: Figure 1 As shown; according to Figure 1 It can be seen that it possesses good thermal stability. The powder X-ray diffraction of the SiFSIX-dpm-Cu layered MOF material obtained in this embodiment after being placed in water / air for one week is shown in the figure. Figure 2 As shown; according to Figure 2 It can be seen that it has good air and water stability.
[0093] The kinetic curves of the SiFSIX-dpm-Cu layered MOF material obtained in this embodiment for C4 hydrocarbons at 298 K and 1 bar are as follows. Figure 3 As shown; according to Figure 3It can be seen that, under normal temperature and pressure, the diffusion rate of 1,3-butadiene in the material is significantly higher than that of n-butene and isobutene. C4H6 reached adsorption equilibrium only 10 min ago, with an equilibrium adsorption capacity of 2.0 mmol / g; while n-C4H8 and iso-C4H8 diffused very slowly, reaching equilibrium at 300 and 600 min respectively, with equilibrium adsorption capacities of 1.8 and 2.0 mmol / g.
[0094] Example 2
[0095] Using a room-temperature stirring method, 1.0 mmol of 4,4'-methylene bipyridine (170 mg) was dissolved in 10 mL of anhydrous methanol. Separately, 0.50 mmol of copper tetrafluoroborate hydrate (118.5 mg) and 0.50 mmol of disodium 1,2-ethanedisulfonate (234 mg) were dissolved in 10 mL of water. The methanol solution of the ligand was added dropwise to the aqueous solutions of the metal salt and anionic salt. The reaction was stirred at room temperature for 24 h to obtain a mixed solution of blue-violet solid products. The liquid was then filtered, and the solid product was soaked in anhydrous methanol for three days, with the methanol solution replaced daily. After drying and degassing under vacuum (<1 Pa) at 373 K for 24 h, the EDS-dpm-Cu layered MOF material was obtained.
[0096] The thermogravimetric curve of the EDS-dpm-Cu layered MOF material obtained in this embodiment is as follows: Figure 4 As shown; according to Figure 4 It can be seen that it possesses high thermal stability. The powder X-ray diffraction of the EDS-dpm-Cu layered MOF material obtained in this embodiment after being placed in water / air for one week is as follows: Figure 5 As shown; according to Figure 5 It can be seen that it has good air and water stability.
[0097] The kinetic curves of the EDS-dpm-Cu layered MOF material obtained in this embodiment for C4 hydrocarbons at 298 K and 1 bar are as follows. Figure 6 As shown; according to Figure 6 It can be seen that, under normal temperature and pressure, the diffusion rate of butadiene in the material is significantly higher than that of n-butene and isobutene. C4H6 rapidly reaches adsorption equilibrium (<100 min), with an equilibrium adsorption capacity of approximately 1.86 mmol / g; n-C4H8 diffuses more slowly, approaching equilibrium after about 1000 min, with an equilibrium adsorption capacity of 1.92 mmol / g; while iso-C4H8 diffuses the slowest, failing to reach equilibrium even after 5000 min, with an adsorption capacity of 1.52 mmol / g at this point.
[0098] Example 3
[0099] Using a room-temperature stirring method, 1.0 mmol of 4,4'-methylene bipyridine (170 mg) was dissolved in 10 mL of anhydrous methanol, and 0.50 mmol of copper tetrafluoroborate hydrate (118.5 mg) and 0.50 mmol of disodium methanedisulfonate (220 mg) were dissolved in 10 mL of water. The methanol solution of the ligand was added dropwise to the aqueous solutions of the metal salt and anionic salt, and the reaction was stirred at room temperature for 24 h to obtain a mixed solution of blue-violet solid products. The liquid was then filtered, and the solid product was soaked in anhydrous methanol for three days, with the methanol solution being replaced once a day during this period. After drying and degassing under vacuum (<1 Pa) at 373 K for 24 hours, the MDS-dpm-Cu layered MOF material was obtained.
[0100] The thermogravimetric curve of the MDS-dpm-Cu layered MOF material obtained in this embodiment is as follows: Figure 7 As shown; according to Figure 7 It can be seen that it possesses high thermal stability. The powder X-ray diffraction of the MDS-dpm-Cu layered MOF material obtained in this embodiment after being placed in water / air for one week is shown in the following figures. Figure 8 As shown; according to Figure 8 It can be seen that it has good air and water stability.
[0101] The kinetic curves of the MDS-dpm-Cu layered MOF material obtained in this embodiment for C4 hydrocarbons at 298 K and 1 bar are as follows. Figure 9 As shown; according to Figure 9 It can be seen that, under normal temperature and pressure, the diffusion rate of butadiene in the material is significantly higher than that of n-butene and isobutene. C4H6 rapidly reaches adsorption equilibrium (<5 min), with an equilibrium adsorption capacity of approximately 1.80 mmol / g; n-C4H8 diffuses more slowly, approaching equilibrium in about 20 min, with an equilibrium adsorption capacity of 1.73 mmol / g; while iso-C4H8 diffuses the slowest, approaching equilibrium in about 200 min, with an equilibrium adsorption capacity of 2.0 mmol / g.
[0102] Example 4
[0103] The SiFSIX-dpm-Cu obtained in Example 1 was packed into a 5 cm long fixed-bed adsorption column. A mixed gas of 1,3-butadiene: n-butene: isobutene:He (volume ratio 50:15:30:5) was introduced into the adsorption column at room temperature at a flow rate of approximately 0.3 mL / min. Both iso-C4H8 and n-C4H8 effluented immediately, and C4H6 effluented from the packed column only after approximately 140 min. Before 1,3-butadiene breakthrough (before 140 min), the volume fraction of 1,3-butadiene in the C4 material flowing from the bed was less than 0.01%, indicating that this invention can achieve efficient removal of 1,3-butadiene from C4 mixed hydrocarbons. When 1,3-butadiene breakthrough occurred, adsorption was stopped, and desorption using He gas purging at approximately 80°C for approximately 5 h yielded high-purity 1,3-butadiene, with a cumulative butadiene purity of 81.56% in the desorbed gas. If collection begins after 30 minutes, a high-purity C4H6 product with a purity greater than 99.5% (polymer grade) can be obtained; after 70 minutes, a high-purity C4H6 product with a cumulative purity greater than 99.99% can be obtained. The adsorption column maintains its desorption performance and can be recycled.
[0104] The penetration curve in this embodiment is as follows: Figure 10 As shown, both iso-C4H8 and n-C4H8 flowed out immediately, showing a slow upward trend. It was not until about 140 minutes later that C4H6 flowed out of the packed column and quickly reached adsorption equilibrium.
[0105] Example 5
[0106] The EDS-dpm-Cu obtained in Example 2 was packed into a 5 cm long fixed-bed adsorption column. A mixed gas of 1,3-butadiene: n-butene: isobutene:He (volume ratio 50:15:30:5) was introduced into the adsorption column at a flow rate of 0.65 mL / min at room temperature. iso-C4H8 immediately effluented, followed by n-C4H8, and C4H6 only effluent from the packed column after approximately 64 minutes. Before 1,3-butadiene breakthrough (64 minutes prior), the volume fraction of 1,3-butadiene in the C4 material flowing from the bed was less than 0.01%, indicating that the present invention can achieve efficient removal of 1,3-butadiene from C4 mixed hydrocarbons. When 1,3-butadiene breakthrough occurred, adsorption was stopped, and desorption using He gas purging at approximately 90°C for about 5 hours yielded high-purity 1,3-butadiene, with a cumulative butadiene purity of 97.66% in the desorbed gas. If collection begins after 85 minutes, a high-purity C4H6 product with a purity greater than 99.5% can be obtained; after 100 minutes, a high-purity C4H6 product with a cumulative purity greater than 99.99% can be obtained.
[0107] The penetration curve in this embodiment is as follows: Figure 11As shown, iso-C4H8 immediately effluxed from the adsorption column, while n-C4H8 and C4H6 penetrated and gradually reached equilibrium at 16 and 64 min, respectively, indicating that the material has a good practical separation effect on the C4 hydrocarbon mixture system.
[0108] Example 6
[0109] The MDS-dpm-Cu obtained in Example 3 was packed into a 5 cm long fixed-bed adsorption column. A mixed gas of 1,3-butadiene: n-butene: isobutene:He (volume ratio 50:15:30:5) was introduced into the adsorption column at a flow rate of 0.65 mL / min at room temperature. iso-C4H8 eluted first, followed by n-C4H8, and C4H6 eluted from the packed column approximately after 62 minutes. Before 1,3-butadiene breakthrough (62 minutes prior), the volume fraction of 1,3-butadiene in the C4 material eluting from the bed was less than 0.01%, indicating that this invention can achieve efficient removal of 1,3-butadiene from C4 mixed hydrocarbons. When 1,3-butadiene breakthrough occurred, adsorption was stopped, and desorption was performed by purging with He gas at approximately 80°C for about 10 hours to obtain high-purity 1,3-butadiene. The cumulative purity of butadiene in the desorbed gas reached 97.59%. If collection begins after 30 minutes, a high-purity C4H6 product with a purity greater than 99.5% can be obtained; after 70 minutes, a high-purity C4H6 product with a cumulative purity greater than 99.99% can be obtained.
[0110] The penetration curve in this embodiment is as follows: Figure 12 As shown, iso-C4H8 and n-C4H8 penetrated at 35 and 40 min respectively. Subsequently, possibly due to competitive adsorption, C4H6 gradually occupied the active site, "squeezing out" iso-C4H8 and n-C4H8. C4H6 then began to penetrate at 62 min and gradually reached equilibrium.
[0111] Example 7
[0112] The C4 fraction from catalytic cracking contains no more than 0.5% C4H6, which needs to be removed to avoid coking in the equipment, while minimizing the adsorption of other C4 hydrocarbon components. Based on this premise, the SiFSIX-dpm-Cu obtained in Example 1 was packed into a 5 cm long fixed-bed adsorption column. A mixed gas of 1,3-butadiene:n-butene:isobutene:He (volume ratio 0.5:10:15:74.5) was introduced into the packed column at a flow rate of 14.0 mL / min at room temperature. Both iso-C4H8 and n-C4H8 effluxed immediately and quickly reached equilibrium. C4H6 only began to permeate after approximately 133 min. The calculated dynamic adsorption capacity of SiFSIX-dpm-Cu for C4H6 was 1.61 mmol / g, while dynamic exclusion was observed for n-C4H8 and iso-C4H8, with dynamic adsorption capacities of approximately 0.07 and 0.04 mmol / g, respectively. Before 1,3-butadiene breakthrough (133 min prior), the volume fraction of 1,3-butadiene in the C4 material flowing out of the bed was less than 0.01%, indicating that the present invention can achieve efficient removal of 1,3-butadiene from C4 mixed hydrocarbons. The adsorption column maintains its desorption performance and can be recycled.
[0113] The penetration curve in this embodiment is as follows: Figure 13 As shown, both iso-C4H8 and n-C4H8 flowed out immediately and quickly reached equilibrium. It was only after about 133 minutes that C4H6 began to penetrate.
[0114] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. The application of metal-organic framework materials as 1,3-butadiene adsorbents, characterized in that, The general structural formula of the metal-organic framework material is shown in Formula I: ML2(A) Formula I; In formula I: A is SiF6 2- GeF6 2- MDS 2- and EDS 2- At least one of them; M is Cu 2+ ; L is an organic ligand, with the structural formula shown in Formula II: Formula II; In Equation II: R1~R8 are all H; The metal-organic framework material has a layered two-dimensional structure; The adsorption is performed on 1,3-butadiene in a mixture of C4 hydrocarbons.
2. A method for adsorption separation of a mixture of C4 hydrocarbons, characterized in that, Includes the following steps: A metal-organic framework material is used as an adsorbent to adsorb and separate 1,3-butadiene from a mixture of C4 hydrocarbons; the mixture of C4 hydrocarbons includes 1,3-butadiene, and also includes at least one of n-butene, isobutene, n-butane, isobutane, cis-2-butene, and trans-2-butene. The general structural formula of the metal-organic framework material is shown in Formula I: ML2(A) Formula I; In formula I: A is SiF6 2- GeF6 2- MDS 2- and EDS 2- At least one of them; M is Cu 2+ ; L is an organic ligand, with the structural formula shown in Formula II: Formula II; In Equation II: R1~R8 are all H; The metal-organic framework material has a layered two-dimensional structure.
3. The method according to claim 2, characterized in that, The adsorption separation temperature is -20~100 ℃ and the pressure is 0~1000 kPa.
4. The method according to claim 2, characterized in that, The metal-organic framework material is an amorphous particle, spherical particle, columnar particle, or membrane.
5. The method according to claim 2, characterized in that, The adsorption separation method is one or more of fixed bed adsorption, fluidized bed adsorption, moving bed adsorption, simulated moving bed adsorption, and membrane separation.
6. The method according to claim 2, characterized in that, The synthesis methods of the metal-organic framework materials include solid-state grinding, interfacial slow diffusion, solvothermal method, room temperature coprecipitation method, or microwave synthesis method.
7. The method according to claim 6, characterized in that, The solvothermal method includes: reacting organic ligand L, anion A, and metal ion M in a liquid reaction system to obtain the metal-organic framework material; the metal ion M is added in the form of a soluble salt containing metal ion M; the anion A is added in the form of a soluble salt or acid containing anion A.
8. The method according to claim 7, characterized in that, The reaction temperature is -20 to 100 °C, and the time is 0 to 48 h, and is not 0.
9. The method according to claim 2, characterized in that, After the adsorption separation, the method further includes desorbing the adsorbent to obtain butadiene-rich product; the desorption method includes desorption under reduced pressure, desorption under elevated temperature or gas purging.
Citation Information
Patent Citations
Method for preparing isobutylene by using adsorption separation method
CN102329180A
Method for purifying butene by adsorption with molecular sieves in liquid-phase state
CN102351630A
Process for separating n-butene and isobutene based on carbon molecular sieve adsorption
CN104030874A
Separation method of C4 alkene mixture
CN109420480A
Adsorbent for separating normal and isohydrocarbon mixture, preparation method of adsorbent and method for adsorbing and separating normal and isohydrocarbon mixture
CN114433028A